Yield and Nutrient Uptake of Green Gram (Vigna Radiata L.) and Weeds as Influenced by Different Integrated Weed Management Practices in Western Uttar Pradesh - Singh, Pooja; Vivek; Preeti Singh; Akshay Ujjawal; Mausmi Rastogi; Sushmita; Mandvi Srivastava (Indonesian Journal of Agriculture and Environmental Analytics, 2023)
The aim of the study is to assess the performance of post-emergence applications of Imazethapyr and Quizalofop-ethyl in combination with pre-emergence applications of Pendimethalin on green gram (Vigna radiata L.). The results revealed that treatment T2 (weed-free) had the best financial return (Rs 91250 ha-1) and B:C ratio (2.72), while among the herbicides treatments T10 and T8 had the highest net financial return (Rs 92706 ha-1) and B:C ratio (3.14), respectively.